PELATIHAN KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN LITERASI STEAM PADA KURIKULUM MERDEKA DI KEPULAUAN SERIBU - Hapidin, Hapidin; Gunarti, Winda; Pujianti, Yuli (LPPM Universitas Nusa Mandiri, 2025)
Educators in Kepulauan Seribu District, DKI Jakarta, experience challenges in designing and implementing an independent curriculum in Early Childhood Education (ECE), especially in project learning that includes elements of religion, character, identity, literacy, and STEAM. In addition, the lack of curriculum documents in PAUD prompted the need for assistance developing an effective Education Unit Operational Curriculum (KOSP). Through participatory training and mentoring, focusing on improving pedagogical competencies, this service program assists PAUD teachers in preparing learning documents, implementing effective learning, and conducting assessments. The methods used include participatory training, focus discussions, and workshops, encouraging participants to more actively understand, analyze, and apply the STEAM Literacy model in the Merdeka Curriculum. The results of this activity show a significant increase in teacher competence, where the pre-test results show the categories of excellent 8.1%, good 13.5%, sufficient 21.6%, and less 56.8%, while the post-test increased to excellent 48.6%, good 27.1%, sufficient 18.9%, and less 5.4%. The program also provides illustrative examples of concepts, practice videos, and the use of a fun L-STEAM project learning model. Children were more active in learning with loose parts media and natural materials, as evidenced by their enthusiasm during project-based play, despite being supervised by many teachers around them. This program improved PAUD teachers' understanding of curriculum development, learning implementation, and early childhood assessment.